Professional Development for Preschool Teachers: Evidence for Practice - Varol, Filiz; Farran, Dale C.; Bilbrey, Carol; Vorhaus, Elizabeth A.; Hofer, Kerry Guess (My University, 2012)
This article summarizes the findings and implications of a study examining effects of a professional development program for preschool teachers with emphasis on mathematics. © 2012 Taylor and Francis Group, LLC.
Keywords: early childhood education; mathematics; preschool teachers; professional development